2023
DOI: 10.1039/d2nr05698d
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic overview of the differences between the absorbing states and the emitting states in semiconductor perovskite nanocrystals

Abstract: Semiconductor perovskites have been under intense investigation for their promise in optoelectronic applications as well as their novel and unique physical properties. There have been a variety of material implementations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 120 publications
(171 reference statements)
1
21
0
Order By: Relevance
“…From transient absorption spectroscopy, it was recently shown that the absorbing state of the band edge of P NC relaxes to the emitting state on the sub-ps time scale . Moreover, we have recently reviewed the experiments on the absorbing state, which suggest qualitative differences from the emitting state . The main point is that the PL data , from these systems is consistent with an excitonic response.…”
Section: Resultsmentioning
confidence: 82%
“…From transient absorption spectroscopy, it was recently shown that the absorbing state of the band edge of P NC relaxes to the emitting state on the sub-ps time scale . Moreover, we have recently reviewed the experiments on the absorbing state, which suggest qualitative differences from the emitting state . The main point is that the PL data , from these systems is consistent with an excitonic response.…”
Section: Resultsmentioning
confidence: 82%
“…The main point from the structural analysis is that these structures are both very polar with strong electron–lattice couplings, and there is a broad distribution of glassy and low-frequency phonon modes that characterize the system. At 300 K, one generally sees spectral densities rather than well-resolved peaks, consistent with their glassy lattice Figure b shows a linear absorption and PL spectrum of the 15 nm MHP NC.…”
mentioning
confidence: 86%
“…In order to elucidate the origin of the non-Condon behavior of the PL in the CsPbBr 3 pervoskite, we perform ab initio modeling which provides a rationalization of the experimentally observed phenomenon. It has been established that metal halide perovskites (MHPs) are soft materials that can undergo significant structural changes when subjected to external perturbations, such as light, current, or temperature. ,,,, MHP regions containing defects, such as point defects and grain boundaries, are particularly prone to such a response. …”
mentioning
confidence: 99%
“…Semiconductor metal halide perovskites (MHP) have been under intense investigation for their performance in photovoltaic devices, which was then learned to arise from their remarkable properties such as defect tolerance . This defect tolerance may be related to their glassy ionic lattice which undergoes complex structural dynamics on a distribution of time scales from femtoseconds to picoseconds. Beyond the initial application in light absorptive devices like photovoltaic films, MHP in their nanocrystal (NC) form are now being explored for light emissive applications due to their favorable emissive properties such as having high quantum yields at 300 K, fast radiative recombination, and support for emission from multiexcitons (MX) in addition to emission from excitons (X).…”
mentioning
confidence: 99%
“…As discussed in the Supporting Information, the model has S = 0.4 for the lower state from single NC experiments, while S for the upper state is fitted to the experimental data to obtain its value of 1.5. The coupling of 0.4 was taken from literature measurements of coupling to phonons by single NC PL. , At low temperature, the line width narrowing monitors the decay from the upper to the lower excitonic state(s). Only this two-state model well describes both the temperature dependence and the time dependence of the line widths at the single exciton level.…”
mentioning
confidence: 99%